THE ROLE OF HAYDER ALIYEV IN THE DEVELOPMENT OF THE AZERBAIJAN LANGUAGE - Farzaliyeva Matanat Cherkaz (Research Retrieval and Academic Letters, 2023)
The article talks about the great services of the national leader Heydar Aliyev in the development of the Azerbaijani language, his national language policy since the beginning of the 70s, the struggle for our language to receive the status of the State language and rise to the international level. Language is the most perfect and most important means of communication. Through this invaluable communication, people understand each other, express their feelings and excitement. Through language, which is the key to the treasury of ideas, people convey the knowledge and experiences they have gained about life to the next generation, passing it on from history to history. Through language, economic, political, cultural and friendly relations between different peoples and countries are created and developed. The Azerbaijani language is the national language of the 50 million Azerbaijani people living in the world, and the official state language of the Republic of Azerbaijan. The Azerbaijani language has an ancient and rich history, tradition, colorful language facts, a developed phonetic, lexical and grammatical system, multifaceted and comprehensive styles. The Azerbaijani language belongs to the family of Turkic languages, Oghuz group of Turkic languages. The Azerbaijani language, which rose to the level of the state language with the establishment of the Safavid state, already had an ancient and rich history of formation from that period. The Azerbaijani language has passed a complex path for hundreds of years, until it was formed on the basis of a universal spoken language of Turkic origin and turned into an oral literary language, and later, on this basis, the written branch of the Azerbaijani literary language was formed.